IMPROVEMENT OF TECHNICAL AND TACTICAL ACTIONS OF YOUNG WRESTLERS (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the improvement of wrestling technical skills, participation of wrestlers in competitions, mastering of wrestling methods, technical-tactical and preparation. Also, during the competitions, the use of wrestling methods, the physical and mental preparation of wrestlers, the application of anti-aging methods to the opponent's actions, the most and perfectly performed methods, and the physiological capabilities of wrestlers were scientifically researched.